2018
DOI: 10.1163/22941932-20170211
|View full text |Cite
|
Sign up to set email alerts
|

Effects of auxin-transport-inhibitor and defoliation on wood formation in locally-heated Abies homolepis

Abstract: To understand the precise process of wood formation, it is necessary to identify the factors that regulate cambial activity and development of cambial derivatives. Here, we investigated the combined effects of localized-heating and auxin on cambial reactivation and the formation of earlywood tracheids in seedlings of the evergreen coniferAbies homolepisin winter. Three treatments were applied, namely heating (artificial increase in temperature 20–22 °C), heating-plus-auxin transport inhibitor N-(1-naphthyl) ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Our present results show that the timing of cambial reactivation and the threshold maximum temperature for C. pisifera stems differed from those of Cryptomeria japonica, even though the trees were grown at the same location in Tokyo, Japan. Similarly, localized heating of the stems of C. pisifera induced cambial reactivation in winter but heating of longer duration was required for cambial reactivation than in other conifers such as Cryptomeria japonica 39 . Thus, it appears that differences among species in the responses of cambium to rising temperatures might be closely related to species-specific sensitivity to temperature of the cambium as it changes from a dormant to an active state.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Our present results show that the timing of cambial reactivation and the threshold maximum temperature for C. pisifera stems differed from those of Cryptomeria japonica, even though the trees were grown at the same location in Tokyo, Japan. Similarly, localized heating of the stems of C. pisifera induced cambial reactivation in winter but heating of longer duration was required for cambial reactivation than in other conifers such as Cryptomeria japonica 39 . Thus, it appears that differences among species in the responses of cambium to rising temperatures might be closely related to species-specific sensitivity to temperature of the cambium as it changes from a dormant to an active state.…”
Section: Discussionmentioning
confidence: 95%
“…When the air temperature starts to rise from late winter to early spring, dormant cambium becomes active under natural conditions 6,7 . Moreover, an artificial increase in the temperature of stems during cambial dormancy in winter induced cambial reactivation in several experimental conifers [31][32][33][34][35][36][37][38][39][40] , a diffuse-porous hardwood 41 and a ring-porous hardwood 42 . Thus, an increase in temperature from late winter to early spring has been clearly demonstrated to be a direct trigger for cambial reactivation in temperate trees 6,7 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the cambial region was defined as the zone with all layers of meristematic cells and the identical in shape intermediate derivatives (Rossi et al., ; Dié et al., ). Cambial cells were distinguished from expanding xylem and phloem cells on the basis of their smaller radial diameter and occurrence of division plates as visualized in epoxy‐embedded 1‐μm‐thick transverse sections (Kitin et al., ; Begum et al., , ; Kudo et al., ; Rahman et al., , ). When cambial cells lose their ability to divide, they start to expand for differentiation into xylem cells.…”
Section: Methodsmentioning
confidence: 99%
“…The periodicity of the activity and dormancy of cambium in temperate trees is closely associated with seasonal changes in temperature, precipitation, and day length (Denne and Dodd, ; Ren et al., ). Recent studies have revealed that the timing of the resumption of cambial cell division, from late winter to early spring, is controlled by increases in temperature (Barnett and Miller, ; Oribe et al., , , ; Schmitt et al., ; Gričar et al., ; Begum et al., , ; Kudo et al., ; Rahman et al., , ). Higher temperatures from late winter to early spring induce earlier resumption of cell proliferation in the cambium and, as a consequence, earlier onset of the differentiation of xylem cells in conifers and hardwoods (Rossi et al., ; Begum et al., , ; Deslauriers et al., ; Kudo et al., ).…”
mentioning
confidence: 99%